EKSPERIMENTASI PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DENGAN MENGGUNAKAN MEDIA KOMPUTER TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KREATIVITAS BELAJAR SISWA - Juniarto, Suci; Mardiyana, Mardiyana; Usodo, Budi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The purpose of this research was to determine the effect model of learning and creativity of students learning the mathematics achievement. The research was quasi experimental. The population of this research was all students of grade VIII SMP/ MTs Muhammadiyah of the District Surakarta, academic year 2011/2012. Instruments used to collect data were mathematics achievement instrument test and questionnaires creativity students toward mathematics instrument. Data analysis technique used hypothesis test with two-way analysis of variance with unbalanced cells resume test of double comparisons. From the results of the analysis, can be concluded that: 1) the learning achievement in mathematics of the students who were learning mathematics with cooperative learning model NHT computer-assisted media were better than the with cooperative NHT and conventional, however the students who were learning mathematics with cooperative learning model NHT were better than the with conventional, 2) the learning achievement in mathematics of the students with the high learning creativity were better than the ones with the medium and low, however the students with the medium learning creativity were betterÂ than the ones with the low, 3) in the cooperative learning model NHT computer-assisted media, the learning achievement in mathematics of the students with ones who have the high learning creativity were better than the students with the low learning creativity, students with the high learning creativity were as good as the ones who have medium learning creativity, and students with the medium learning creativity were as good as the ones who have low learning creativity as well. In the cooperative learning model NHT and conventional, the students with the high, medium, and low learning creativity had the same achievement in learning mathematics, 4) in the students with the high learning creativity, the learning achievement of the students who were learning mathematics with ones who have cooperative learning model NHT computer-assisted media were better than the students were learning mathematics with cooperative NHT, the students who were learning mathematics with cooperative NHT had the same achievement in learning mathematics with conventional, and the students who were learning mathematics with cooperative learning model NHT computer-assisted media had the same achievement in learning mathematics with cooperative NHT. The students with the medium and low learning creativity had the same achievement in learning mathematics among the ones who were given the cooperative learning model NHT computer-assisted media, NHT, and conventional on solid geometry.Key words: Numbered Heads Together (NHT), Computer media, Conventional Learning Model, Learning Creativity, Achievement Learning Mathematics.